Estudo psicológico de pacientes obesas mórbidas com transtorno da compulsão alimentar periódica, pós cirurgia bariátrica, em psicoterapia grupal breve, com abordagem Junguiana - Costa, Maria Bernadete de Lourdes Brito (2009)
Obesity is growing among the population in general, a fact which brings serious consequences to a person s physical and mental health. As it is considered a public health problem in Brazil, Bariatric Surgery has been revealing itself as a useful tool in the treatment of morbid obesity. Many studies have shown that excess weight tends to diminish life expectancy and leads to a predisposition for morbidity, the reduction of motor activities, tiredness, a worsening of the quality of life and a rise in problems related to the human psyche. The purpose of this study is to observe and reflect on the psychological effects of the short, focal, group psychotherapy, with a Jungian orientation in morbid obese patients, with periodic eating compulsion disturbance, after bariatric surgery. This treatment will help them in the maintenance of the surgery gains, in other words, weight maintenance, and awareness concerning eating, the body, and periodic eating compulsion, offering a better life quality and also more satisfactory. Six morbid obese patients, just after bariatric surgery, with periodic eating compulsion disturbances took part in the research. They answered the Semi-Structured, Brief interview, (MINI - INTERNATIONAL NEUROPSYCHIATRIC INTERVIEW) and the Scale of Periodic Eating Compulsion (SPEC ECAP), before and after the twelve sessions of group focal psychotherapy, on the themes already proposed. The session was carried out in the attendance room in the Outpatient s department of the Teaching and Research Foundation in Uberaba, an organ linked to the Federal University of the Triângulo Mineiro. The twelve psychotherapy sessions were taped, transcribed and analysed through the test, which verified the words which were most frequently used in the sentences of the patients discourse. The patients development during the proposed therapy was analyzed and shown in graphs. The MINI test showed some small differences which do not interfere in the life experiences of the patients, and does not show any psychiatric disturbance of any intensity which would alter their lives, becoming prejudicial to them. The SPEC (ECAP) showed tendencies to eating compulsion which can be controlled and do not interfere in re-education. The patients propose to continue the treatment after the research. The results show how the psychological part of the participants works after bariatric surgery and the twelve psychotherapy sessions, highlighting changes in the life quality, as well as making life more healthy and satisfactory. It was confirmed that all the participants became aware of the need to love themselves better. It was a rewarding and totally new situation confirmed after Bariatric Surgery